Green synthesis of iron oxide nanoparticles using Thymus migricus for multifunctional applications in antioxidant, antimicrobial, photocatalytic, and seed priming processes - Sanaz Ashrafi-Saiedlou; MirHassan Rasouli-Sadaghiani; Mohammad Fattahi (Heliyon)
Iron oxide nanoparticles (Fe2O3NPs) with an average diameter of 14.74 ± 0.23 nm were synthesized through a green synthesis method using the extract of Thymus migricus. Fe2O3NPs was thoroughly characterized using various techniques including UV–Vis, XRD, FTIR, FESEM, EDX, TEM, BET and DLS. The study investigated the photocatalytic, antimicrobial, antioxidant, and seed priming properties of Fe2O3NPs. The photocatalytic potential of Fe2O3NPs (0.5 mg mL−1) was assessed against methyl orange (MO), methyl violet (MV), and methylene blue (MB) dyes exhibiting degradation rates of 64.5 %, 84.6 %, and 61 %, respectively. The antibacterial activity of Fe2O3NPs was examined against one Gram-positive bacterial strain (Staphylococcus aureus) and three Gram-negative bacterial strains (Escherichia coli, Pseudomonas syringae, and Salmonella enterica). Considerable growth inhibition was observed in S. aureus and S. enterica, with inhibition zone diameters of 16.15 ± 0.19 mm and 13.31 ± 0.46 mm, respectively, with 400 μg mL−1 Fe2O3NPs. The IC50 value (2.85 ± 0.29 μg mL−1) for the antioxidant activity of the synthesized NPs was determined by DPPH free radical scavenger assay. The exceptional biomedical potential of NPs was attributed to their remarkably small size. The research findings demonstrated the efficacy of synthesizing iron nanoparticles from plants. These results have the potential for application in pharmaceuticals, food, and various other industries following additional studies.